2014
DOI: 10.1007/s00391-014-0832-5
|View full text |Cite
|
Sign up to set email alerts
|

Tablet-PC und ihr Nutzen für demenzerkrankte Heimbewohner

Abstract: The use of tablet computers was convincing as an activation therapy for nursing home residents with dementia. Further research and development of specially adapted software are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“… Cross-sectional N/A 93 Qualitative studies [ 55 ] Bär et al 2003 Identification of characteristic situations accompanied by positive emotions Qualitative N/A 29 [ 60 ] Becker et al 2006 Identification and cross-validation of patterns of competence in nursing home residents. Qualitative N/A 362 [ 92 ] Nordheim et al 2015 Evaluation of the use of tablet PCs in PwD in NH Qualitative 1 14 AD Alzheimer’s disease, C-RCT Cluster-randomized controlled trial, CT controlled trial, N/A not available, NHs nursing homes, P Participants, PwD People with dementia, RCT Randomized controlled trial a The number of participants reported from this international study refers to the German sample only …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Cross-sectional N/A 93 Qualitative studies [ 55 ] Bär et al 2003 Identification of characteristic situations accompanied by positive emotions Qualitative N/A 29 [ 60 ] Becker et al 2006 Identification and cross-validation of patterns of competence in nursing home residents. Qualitative N/A 362 [ 92 ] Nordheim et al 2015 Evaluation of the use of tablet PCs in PwD in NH Qualitative 1 14 AD Alzheimer’s disease, C-RCT Cluster-randomized controlled trial, CT controlled trial, N/A not available, NHs nursing homes, P Participants, PwD People with dementia, RCT Randomized controlled trial a The number of participants reported from this international study refers to the German sample only …”
Section: Resultsmentioning
confidence: 99%
“…A broad range of cutoff scores for dementia severity was reported for the MMSE. Seven studies referred to an MMSE of < 25 [ 37 , 40 , 48 51 ], 6 studies used a cutoff of ≤ 24 [ 85 90 ], 8 articles referred to a cutoff of < 24 to detect mild dementia [ 76 80 , 82 , 91 , 92 ], and 4 articles referred to a more conservative cutoff. [ 39 , 41 , 83 , 93 ] One article specified a higher cutoff value of ≤ 27 but conducted confirmatory testing with the Geriatric Depression Scale (GDS) for residents with an MMSE between 24 and 27 [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…websites and web applications, and also primarily focused on elderly people in general and not on people with cognitive impairments. Although there is growing evidence that people with dementia are able to use a tablet and its apps, 24,26,28,37,38 evidence of the importance of diversity regarding functional and technical features of apps for the successful use of tablets by people with dementia is still very scarce. To our knowledge, this study is the first of this kind.…”
Section: Discussionmentioning
confidence: 99%
“…Although people with dementia will need support to learn how to use the touchscreen and apps, 2329 several mainly qualitative studies have shown that those who used the tablet and its apps evaluated it as user-friendly and valuable. 2438 The tablet and its apps may therefore be promising tools in supporting self-management activities 21,24 and engaging in meaningful activities 26,39 in the early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies, including two RCTs, focus on cognitive stimulation with predominantly positive results. [96][97][98][99] Two studies tested serious games with a quasi-experimental design aiming mainly at physical improvements in inpatient long-term care settings. While one of the studies reported positive results, 100 the other one found positive results on physical functioning but reported negative effects on emotional performance as a study result.…”
Section: Systems To Support Process Planning And/or Data Exchangementioning
confidence: 99%